Relationship between Frequency of Sugar Sweetened-Beverages (SSB) Consumption and Prediabetes: Aim For Screening Prediabetes Among Medical Students - Nasution, Huwainan Nisa; Febriyanti, Eka; Suryani, Des (Buletin Farmatera, 2022)
Sugar sweetened-beverages (SSB) is not only found in soft drinks, fruit juice drinks, or energy drinks, but also various drinks that are currently "trending" such as boba drinks with various flavors, coffee or milk coffee, even tea or milk tea with various flavors. The lifestyle of consuming drinks that are high in sugar will lead to a tendency to several diseases such as prediabetes, diabetes mellitus (DM), metabolic syndrome and cardiovascular disease. Prevention and screening of prediabetes and DM at a young age in Indonesia must be increased, especially in high-risk groups because most of the initial conditions of the disease are asymptomatic. The aim of this study is to analyze the association between frequency of sugar sweetened-beverages (SSB) consumption and prediabetes in medical students. This study was an observational analytic study with cross sectional design conducted at Medical Faculty Universitas Muhammadiyah Sumatera Utara. The subjects of this study was 70 subjects. Examination of frequency of SSB consumption was carried out with a validated questionnaire and food frequency questionnaire (FFQ) of nutrient intake for the past 24 hours. There is no significant relationship between gender, family history of DM, smoking history, physical activity and hypertension with prediabetes. However, there is a significant relationship between obesity and prediabetes with p value 0,010. Meanwhile, the relationship between frequency of SSB consumption and prediabetes showed with p 0.05. There is no significant relationship between frequency of SSB consumption and prediabetes, but there is significant relationship between obesity and prediabetes.